The effectiveness of back belts in reducing the incidence, duration and cost of low back pain claims associated with manual handling injury in a retail hardware chain - Merdith, Nick; Oosthuizen, J.; Nedved, M. (CCH Australia Limited, 2011)
The objective of this intervention study was to examine the effect of the mandatory introduction of back belts on the incidence, days lost and cost of occupational low back injuries resulting from manual handling in a retail hardware chain in Western Australia. The pre-intervention period extended for 21 months and included 2,265,933 work hours or 647 lull-time equivalent positions, while the intervention period was 32 months for 4,411,352 hours worked or 827 full-time equivalent positions. Workers' compensation claims for all occupational injuries occurring during the study period were analysed. During the intervention period there was a 14% reduction in the incidence frequency rate for all low back pain claims and a 33% reduction in those low back pain claims resulting in lost time, but neither reduction was statistically significant. The introduction of the back belts was followed by a significant 69% reduction in the average days lost per low back pain claim and a 79% reduction in the days lost to low back pain per hours worked. The average direct cost was reduced by 77% for all low back pain claims and 74% for low- back claims resulting in lost time, and 80% and 83% respectively when analysed per hours worked.The mandatory use of back belts was associated with a reduction in both the days lost and cost of occupational low back pain resulting from manual handling, and back belts may provide a cost-effective control tor occupational low back pain if high compliance is maintained